Static and dynamic behaviour of ultra high molecular weight poly-ethylene (UHMWPE) Tensylon® composite - Magali Castres; Aboulghit El Malki Alaoui; Camille Caisso; Martin Monloubou; Michel Arrigoni (eXPRESS Polymer Letters)
Nowadays, ultra high molecular weight polyethylene (UHMWPE), allows the combination of lightweight, high strength and is praised for the design of severely loaded structures. It has become a good option for lightweight armour solutions. It is therefore important to characterise its mechanical behaviour. Up to now, strain rate effects on mechanical behaviour have been poorly explored. In this work, this issue is tackled by studying the strain rate influence on the in-plane deformation, in shear and tension of the Tensylon® HSBD30A, a UHMWPE dedicated to ballistic and blast protection. Two laminates of Tensylon® of respective orientation [0 °/90°]20 and [±45°]20 were subjected to static and split Hopkinson tensile bar (SHTB) tests. A new mounting system was designed, and new specimen shapes were used to match the experimental setup configurations. Digital image correlation (DIC) was used to measure the in-plane strain. A significant strain-rate dependence on the material behaviour.is evidenced. Besides, results exhibit a higher strength for the [0°/90°]20 specimen than for the [±45°]20 one. Despite some limitations, the proposed setup and measurement methods allowed visualisation of strain rate effects on the stress-strain relationship for strain rates ranging from the quasi-static regime to the dynamic one (1500 s–1).